1996
DOI: 10.1136/gut.38.2.229
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial comparing mesalazine and prednisolone foam enemas in patients with acute distal ulcerative colitis.

Abstract: Distal ulcerative colitis can be treated with oral or rectal mesalazine, or both. A foam enema preparation has been developed and its efficacy investigated. The aim of this study was to evaluate the efficacy and safety of mesalazine foam enemas compared with prednisolone foam enemas in the treatment of patients with acute distal ulcerative colitis. Patients aged over 18 years presenting with a relapse of distal ulcerative colitis were randomly allocated treatment with mesalazine foam enema (n = 149 evaluable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 12 publications
1
47
0
3
Order By: Relevance
“…Remission was defined as clinical improvement that resulted in a bowel frequency of not more than 3 times per day and no rectal bleeding. 18 Relapse was defined as a change in the clinical status that entailed more aggressive treatment in patients in remission. 19 Proximal disease extension was defined as the extension, at any follow-up colonoscopy, of macroscopic inflammation beyond the initially involved segment, that is, from proctitis to left-sided or extensive colitis or from left-sided colitis to extensive colitis.…”
Section: Methodsmentioning
confidence: 99%
“…Remission was defined as clinical improvement that resulted in a bowel frequency of not more than 3 times per day and no rectal bleeding. 18 Relapse was defined as a change in the clinical status that entailed more aggressive treatment in patients in remission. 19 Proximal disease extension was defined as the extension, at any follow-up colonoscopy, of macroscopic inflammation beyond the initially involved segment, that is, from proctitis to left-sided or extensive colitis or from left-sided colitis to extensive colitis.…”
Section: Methodsmentioning
confidence: 99%
“…29,45,53,83,85,[90][91][92] Histological improvement has been reported after oral budesonide therapy (47% of patients with UC in a review including three randomized controlled trials) 92 and also after aminosalicylates, occasionally achieving histological remission. 46,82,84,86,88,89 In a Cochrane review, rectal 5-ASA was superior to placebo for inducing histologic improvement (OR 7.69 p b 0.0001) and remission (OR 6.28 p b 0.0001) in the 6/38 trials using histopathology as a secondary or post-hoc endpoint.…”
Section: Relapse Surgery Mortalitymentioning
confidence: 97%
“…Patients with active distal UC can be treated with rectal 5-ASA (enemas, foams, or suppositories), oral 5-ASA, or a combination of both. Several controlled trials have shown that rectal therapies have a more rapid effect than oral treatment [12,13] . Meta-analysis of the published data showed that rectal 5-ASA is superior to placebo and to conventional rectal corticosteroids for inducing remission of symptoms, endoscopy, and histology of distal UC [7] .…”
Section: Treatment Of the Acute Phasementioning
confidence: 99%